Preliminary Study on Anxiety Levels Among Palm Oil Farmers in Simpang Pematang District, Mesuji Regency-Lampung Province (2024) - Bachtiar, Nabylly Aghna; Saftarina, Fitria; Larasati, Ratri Mauluti; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2025)
As the world's largest palm oil producer, Indonesia bears a significant responsibility for the well-being of its farmers, including mental health aspects, which remain a pressing issue. Farmers face various occupational pressures that have the potential to trigger psychological disorders, particularly anxiety. Poorly managed anxiety can lead to decreased concentration and productivity. This study aims to describe the anxiety levels experienced by palm oil farmers in Simpang Pematang District, Mesuji Regency, Lampung. A cross-sectional design was employed in this study, utilizing purposive sampling for sample selection. A total of 109 palm oil farmers participated as respondents, and the collected data were analyzed using frequency distribution. The results indicate that 14.7% of farmers exhibited symptoms of anxiety, with 11.9% experiencing mild anxiety and 2.8% experiencing moderate anxiety. No cases of severe anxiety were found among the respondents. Although the overall anxiety level identified in this study was lower than in previous research, it remains a matter of concern. These findings highlight the necessity of continuous efforts to enhance the mental well-being of farmers. Therefore, a more intensive mental health promotion program is required to improve farmers' understanding of stress management strategies. By doing so, farmers are expected to maintain their psychological well-being, ultimately contributing to increased productivity in Indonesia's palm oil agricultural sector.